1989
DOI: 10.1007/bf01536365
|View full text |Cite|
|
Sign up to set email alerts
|

Use of external shock-wave lithotripsy and adjuvant ursodiol for treatment of radiolucent gallstones

Abstract: A prospective multicenter trial was performed to evaluate the use of external shockwave lithotripsy (ESL) and adjuvant medical therapy for the treatment of gallstones. A Medstone STS lithotripter was used together with ursodiol. Two hundred twenty-three patients were treated under general anesthesia (75%) or with intravenous analgesia (25%). Initial treatments were on an inpatient basis, but as centers gained experience, outpatient treatments became more common. Stone fragmentation and clearance were greatest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

1990
1990
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…55% of the patients showed clearance of the gall bladder after 6 months, whereas in patients with larger fragments (> 5 mm) the effect was significantly reduced. Another study [7] and our own results confirm these data.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…55% of the patients showed clearance of the gall bladder after 6 months, whereas in patients with larger fragments (> 5 mm) the effect was significantly reduced. Another study [7] and our own results confirm these data.…”
Section: Discussionsupporting
confidence: 81%
“…New lithotriptors permit shock wave appli cation using either no premedication or only mild sedation and administration of analgesic drugs [1][2][3][4][5]. Despite this, repro ducible short-and long-time results are not yet established [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…No further complications of ESWL needed operative intervention. In other studies, the incidence of cholecystectomy was found to be 8 (4%) of 223 patients [12], 6 (4%) of 135 patients [13], or 6 (8%) of 78 patients [14]. The number of patients with biliary colic was not as high as found by others, but further complications appeared in similar frequencies as found in studies on early results after ESWL [12,13].…”
Section: Discussionsupporting
confidence: 75%
“…The fascinating idea of noninvasive shock-wave litho tripsy of gallstones, which held out great hope at the beginning [72][73][74][75], is now also being restricted to a very selected group of patients [46,76].…”
Section: Esw L O F Gallbladder Stonesmentioning
confidence: 99%
“…Within this small group of patients 80% are stone free after 1 year [46,[72][73][74][75][76][77]79], Patients with multiple (up to 3) and larger stones (up to 30 mm in diameter) have a success rate of only 30-50% within 6-12 months [80]. Again these pa tients generally need an additional long-term treatment with medical litholysis for 8-10 months, and the recur rence of stones, which is frequently associated with the recurrence of biliary pain, occurs in about 23-30% of the patients after 5 years [80,81].…”
Section: Esw L O F Gallbladder Stonesmentioning
confidence: 99%